The Optimazing Instagram Direct Message Using the User-Centered Design Method - Hakim, Muhammad Sulthanul; afifah, afifah trista ayunda (Politeknik Negeri FakFak, 2025)
. Instagram is a social media platform that allows users to share various photos, videos, and messages online. In the digital era, communication through social media has become a means for users to interact. The Direct Message (DM) feature on Instagram plays an important role in facilitating communication. However, based on observations and questionnaire results, users reported that the interface and user experience of this feature are less than optimal, particularly regarding feature functionality, less efficient message management, and difficulties in marking important messages. Based on these issues, this study focuses on understanding user needs to improve the DM feature. Instagram DM serves as an interface that delivers information to users. The purpose of this research is to increase efficiency, create a more interactive user experience, and enhance user satisfaction when using the Direct Message feature on Instagram. This study adopts the User-Centered Design (UCD) method for a design development process oriented to user needs, involving four stages: user analysis, solution analysis, design, and testing. Prototype design testing uses the System Usability Scale (SUS) method to measure system usability. The SUS test results from 37 respondents yielded a score of 71%, indicating a good level of usability and acceptance by users.